Disclosure of violence against women and girls in Senegal - Peterman, Amber; Dione, Malick; Le Port, Agnès; Briaux, Justine; Lamesse, Fatma; Hidrobo, Melissa (International Food Policy Research Institute, 2023)
Measures of violence against women and girls (VAWG) are widely collected in surveys, yet estimates are acknowledged to be lower-bounds of the true prevalence. Disclosure may be affected by numerous factors, including shame and stigma, fear of retaliation, distrust of interviewers or desire to keep the perpetrator's identity confidential. We conduct a survey experiment randomly assigning approximately 3,400 women and girls aged 15 to 35 to either face-to-face interviews or audio computer-assisted self interviews (ACASI). Results show participants in the ACASI group report higher prevalence of lifetime intimate partner violence by 4 to 7 percentage points compared to face-to-face interviews. Differences in reporting for non-partner VAWG are even larger, ranging from 6 to 12 percentage points for physical violence and sexual harassment, respectively. We test for correlates of characteristics which might lead toincreased disclosure, however, we find few notable patterns. Our results suggest that ACASI surveys are a promising way to encourage disclosure, but acknowledge trade-offs that include limits in the complexity of questions that can be asked and higher time costs associated with development and implementation of surveys.